Association of the inflammatory potential of diet and lower urinary tract symptoms among men in the United States. (1st January 2021) - Liao, Xinyang; Bian, Haiyang; Zheng, Xiaonan; Ai, Jianzhong; Yang, Lu; Liu, Liangren; Qiu, Shi; Wei, Qiang
Abstract: Background: Inflammation is crucial in the pathogenesis of lower urinary tract symptoms (LUTS) in men. Diet modulates inflammation. Therefore, diet could be a modifiable factor in male LUTS prevention and treatment. We aimed to investigate the association between dietary inflammatory potential and male LUTS. Methods: We used two cycles of National Health and Nutrition Examination Survey (NHANES) with self-report LUTS data. We calculated the dietary inflammatory index (DII) based on a 24 h diet recall and evaluated male LUTS. Clinical LUTS was defined as two or more coexisting symptoms. We used univariate and multivariate logistic regression models, the smooth curve fitting to analyze the relationship between clinical LUTS and the DII score. Subgroup analyses were conducted. Results: We observed a positive non-linear relationship between clinical LUTS and DII. We found that when DII was higher than the inflection point 2.39, a 1-unit increase in DII was associated with 26.1% higher adjusted odds of clinical LUTS. Subgroup analyses showed that the DII score was only positively correlated with clinical LUTS risk in non-drinkers, smokers, and non-obese people (DII >2.39). Conclusions: Inflammation might be the key mechanism bridging dietary consumption to male LUTS. Excessive pro-inflammatory food intake (DII >2.39) warrants special vigilance, especially for non-drinkers, smokers, and non-obese men.